IDENTIFYING THE IMPACT OF METHANOL-DIESEL FUEL ON THE ENVIRONMENT USING A FOUR-STROKE CI ENGINE - Hassan, Qais Hussein; Alalwan, Hayder; Mohammed, Malik; Mohammed, Mohammed F. (Journal of Applied Engineering Science, 2023)
This work aims to investigate the influence of blending diesel fuel with different percentages of methyl alcohol on reducing the emission of exhaust gases. The study was performed using a laboratory diesel engine, which is an internal combustion, single-cylinder, and four-strokes engine. The study involved investigating three volume percentages of methyl alcohol (methanol), which are 7, 14, and 21. The emission results of the blending fuels were compared with that of non-blending fuel. The analysis of the exhaust gases was done under three engine loads, which are two, four, and six N.m, with a constant speed of 2000 rpm. The analysis involves measuring carbon oxides (CO and CO2), unburned hydrocarbons (HC), nitrogen oxides (NOx), and particulate matter (PM). The results showed a positive impact of methanol on reducing the emission of all gases except NOx. Increasing the methanol ratio increases the reduction of the emissions of CO, CO2, PM, and HC, where the highest reductions of the gaseous emissions were observed with the percentage of 21% of methanol under all engine loads. Specifically, the drop recorded by using 21% of methanol was 69-83% for CO, 60-69% for CO2, 80-83% for HC, and 25-30% for PM. These reductions in emissions are assigned to the high oxygen content of methyl alcohol that influences the complete combustion of diesel. On the other hand, the NOx emission increased by 135-346%, but a possible reduction in these emissions can be achieved through a proper engine modification. The results of this investigation provide essential insights that would inspire using methanol as a fuel additive with modifying the diesel engines to be compatible with blending fuel.